Generalization and Hume's Problem of Induction: Misconceptions and Clarifications - TSANG, Eric W. K. (Institutional Knowledge at Singapore Management University, 2007)
In Generalizing Generalizability in Information Systems Research Lee and Baskerville (2003) attempt to clarify generalization and distinguish four types of generalization. Although this is a useful objective, what they call generalization is often not generalization at all in the proper sense of the word. We elucidate generalization by locating their major errors. A main source of these is their failure to understand the depth of Hume’s problem of induction. We give a thorough explication of the problem and then give a solution. Lastly, we propose an alternative taxonomy of generalization: theoretical, within-population, cross-population, contextual, and temporal.